IMPLEMENTASI MARKET DAY SEBAGAI SARANA PENGUATAN LITERASI KEWIRAUSAHAAN BERBASIS PENDEKATAN DEEP LEARNING - Eka Indi Rahayu; Fitri Puji Rahmawati (Universitas Negeri Medan, 2026)
Abstract: This study aims to examine the implementation of Market Day activities in strengthening entrepreneurial literacy in elementary school students. The research used a qualitative method with a case study approach. It was conducted at Muhammadiyah Alam Surya Mentari Elementary School in Surakarta, involving classroom teachers and students as primary informants. Data were obtained through observation, interviews, and documentation. Their validity was then tested using triangulation techniques and sources. They were then analyzed continuously through a process of organizing data, interpreting findings, and drawing conclusions. The research results show that Market Day activities were implemented in a structured and integrated manner through planning, implementation, and evaluation stages, emphasizing the principles of meaningful, mindful, and joyful learning as the main characteristics of the deep learning approach. The implementation of these activities provided authentic and contextual learning experiences for students and contributed to strengthening entrepreneurial literacy holistically, encompassing aspects of knowledge, attitudes, and skills. In terms of knowledge, students understand basic entrepreneurial concepts such as capital, profit, and the buying and selling process. In terms of attitude, they can foster self-confidence, responsibility, honesty, and courage in decision-making. Meanwhile, in terms of skills, students demonstrate development in communication, collaboration, creativity, and problem-solving skills through experience-based entrepreneurial practices. Thus, Market Day activities based on a deep learning approach are effectively implemented as a contextual, meaningful, and sustainable entrepreneurship learning strategy in elementary schools. Keyword: Deep Learning, Entrepreneurship Literacy, Market Day Abstrak: Penelitian ini bertujuan mengkaji implementasi kegiatan Market Day dalam memperkuat literasi kewirausahaan peserta didik sekolah dasar. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus yang dilaksanakan di SD Muhammadiyah Alam Surya Mentari, Surakarta, dengan melibatkan guru kelas dan peserta didik sebagai informan utama. Data diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian diuji keabsahannya menggunakan triangulasi teknik dan sumber, serta dianalisis secara berkelanjutan melalui proses pengorganisasian data, pemaknaan temuan, dan penarikan simpulan. Hasil penelitian menunjukkan kegiatan Market Day dilaksanakan secara terstruktur dan terintegrasi melalui tahap perencanaan, pelaksanaan, dan evaluasi dengan mengedepankan prinsip meaningful learning, mindful learning, dan joyful learning sebagai ciri utama pendekatan deep learning. Implementasi kegiatan tersebut memberikan pengalaman belajar yang autentik dan kontekstual bagi peserta didik serta berkontribusi dalam memperkuat literasi kewirausahaan secara holistik, meliputi aspek pengetahuan, sikap, dan keterampilan. Aspek pengetahuan, peserta didik memahami konsep dasar kewirausahaan seperti modal, keuntungan, dan proses jual beli. Pada aspek sikap, dapat menumbuhkan kepercayaan diri, tanggung jawab, kejujuran, dan keberanian dalam mengambil keputusan. Sementara itu, pada aspek keterampilan, peserta didik menunjukkan perkembangan kemampuan komunikasi, kolaborasi, kreativitas, dan pemecahan masalah melalui praktik kewirausahaan berbasis pengalaman. Dengan demikian, kegiatan Market Day berbasis pendekatan deep learning efektif diterapkan sebagai strategi pembelajaran kewirausahaan di sekolah dasar secara kontekstual, bermakna, dan berkelanjutan. Kata Kunci: Deep Learning, Literasi Kewirausahaan, Market Day